Potential of Implementing the Low Concentration Photovoltaic Systems in the United Kingdom - Abu-Bakar, S.H.; Muhammad-Sukki, F.; Freier, D.; Ramirez-Iniguez, R.; Mallick, T.K.; Munir, A.B.; Yasin, S.H.M.; Mas’ud, A.A.; Abu-Bakar, S.S.; Bani, N.A.; Muhtazaruddin, M.N. (Institute of Advanced Engineering and Science, 2017)
This paper discusses the prospect of integrating a novel type of low concentration photovoltaic (LCPV) design known as the rotationally asymmetrical compound parabolic concentrator (RACPC) in a building in the United Kingdom. This is done by proposing a number of building integration designs to create a zero carbon building. A cost reduction analysis of installing the LCPV systems in the country is also presented. It was found that an RACPC design could reduce the LCPV module's manufacturing cost by 31.75% and the LCPV module's cost per unit power output by 33.87% when compared with the conventional PV module.